Kyrenia ship - Martins, Adolfo Miguel (iMARECULTURE H2020 Project: Advanced VR, iMmersive serious games and Augmented REality as tools to raise awareness and access to European underwater CULTURal heritagE, 2017)
This detailed 3D model of a late Classical ship was inspired of what we know from the archaeological record. There are several versions of this reconstructed vessel, available in different formats. The present model was developed based on J. Richard Steffy's drawings, with kind permission of Susan Katzev.
Keywords: 3D model; Kyrenia; iMARECULTURE; 3D library